Activation of Neutrophil Granulocytes by Platelet-Activating Factor Is Impaired During Experimental Sepsis - Hug, Stefan; Bernhard, Stefan; Stratmann, Alexander Elias Paul; Erber, Maike; Wohlgemuth, Lisa; Knapp, Christiane Leonie; Bauer, Jonas Martin; Vidoni, Laura; Fauler, Michael; Föhr, Karl Josef; Radermacher, Peter; Hoffmann, Andrea; et al. (Frontiers in Immunology, 2021)
Platelet-activating factor (PAF) is an important mediator for the systemic inflammatory response. In the case of sepsis, proper activation and function of neutrophils as the first line of cellular defense are based on a well-balanced physiological response. However, little is known about the role of PAF in cellular changes of neutrophils during sepsis. Therefore, this study investigates the reaction patterns of neutrophils induced by PAF with a focus on membrane potential, intracellular pH, and cellular swelling under either physiological or pathophysiological conditions and hypothesizes that the PAF-mediated response of granulocytes is altered during sepsis. The cellular response of granulocytes including membrane potential, intracellular pH, cellular swelling, and other activation markers were analyzed by multiparametric flow cytometry. In addition, the chemotactic activity as well as the formation of platelet-neutrophil-complexes after exposure to PAF were investigated. The changes of the (electro-)physiological response features were translationally verified in a human ex vivo whole blood model of endotoxemia as well as during polymicrobial porcine sepsis. In neutrophils from healthy human donors, PAF elicited a rapid depolarization, an intracellular alkalization, and an increase in cell size in a time- and dose-dependent manner. Mechanistically, the alkalization was dependent on sodium-proton exchanger 1 (NHE1) activity, while the change in cellular shape was sodium flux- but not NHE1-dependent. In a pathophysiological altered environment, the PAF-induced response of neutrophils was modulated. Acidifying the extracellular pH in vitro enhanced PAF-mediated depolarization, whereas the increases in cell size and intracellular pH were unaffected. Ex vivo exposure of human whole blood with lipopolysaccharide diminished the PAF-induced intracellular alkalization as well as the change in neutrophil size. During experimental porcine sepsis, depolarization of the membrane potential was significantly impaired. Additionally, there was a trend for increased cellular swelling, whereas intracellular alkalization remained stable. Overall, an impaired (electro-)physiological response of neutrophils to PAF stimulation represents a cellular hallmark of those cells challenged during systemic inflammation. Furthermore, this altered response may be indicative of and causative for the development of neutrophil dysfunction during sepsis.